Evaluasi Program Pendidikan Pemakai Perpustakaan IST AKPRIND Yogyakarta dengan Model Center for the Study of Evaluation – University of California in Los Angeles (CSE-UCLA) - Yusrin Karauna; Anis Masruri (Literatify: Trends in Library Developments, 2023)
The purpose of this study was to evaluate the activities of the user education program at the IST AKPRIND library in Yogyakarta by using a model the CSE-UCLA evaluation which consists of four stages namely;(1) Needs Assessment, (2) Program Planning, (3) Formative Evaluation, (4) Summative Evaluation. This research method is a quantitative descriptive research method. Determination of data source retrieval by means incidental sampling data collection techniques with questionnaires. Respondents in this study were 50 students. The results of the research show that in stages Needs Assessment, focusing on programs, goals and analysis of human resource needs for user education by 97.5% is categorized as very suitable. Program Planning, this stage is related to program materials, program planning, mentors or presenters, students and user education budgets of 94.35% categorized in accordance. Stages Formative Evaluation, regarding the implementation process, implementation suitability, facilities and infrastructure as well as user education monitoring and supervision of 98.37% which are categorized as very appropriate. Then stages Summative Evaluation, an evaluation of the achievement of program objectives and the impact of the user education program of 98.25% is categorized as very appropriate.